KEGIATAN SUNATAN MASSAL PEDULI SESAMA SEKOLAH ISLAM NABILAH TAMAN DUTA MAS KEPADA MASYARAKAT KOTA BATAM - Sarmini; Cevy Amelia; Yuanita Sidabutar; Asnira; Dominggas Talaksoru (LPPM-Universitas Batam, 2024)
The implementation of this community service is to improve children's ability to understand the meaning of their potential which is then applied to their future orientation. This is very good if introduced from an early age, namely children who are already at school and already have optimal creative imagination. This activity supports children's ability to express his aspirations for the future. If trained, it will form character formation that improves psychological well-being in children. This community service is aims to carry out Nabilah's social care (NPS) program, which is an activity of Nabilah's social institution. This mass circumcision activity is carried out every year that is started from 2017 until now. The implementation was carried out during school holidays. This mass circumcision is aimed at Batam City residents aged 5 – 13 years. This activity increases the ability to show solidarity and care for others. Providing knowledge that it is important for boys to be circumcised as a religious obligation and a sign that they have reached puberty. Something that will be useful in the future is from a health perspective, namely physical cleanliness.